Early childhood stress regulation in out-of-home childcare and in at-home parental care – Associations with child temperament and age – The FinnBrain Birth Cohort Study - Tervahartiala, Katja (fi=Turun yliopisto|en=University of Turku|, 2021)
Prior research suggests that attendance in out-of-home childcare has many positive effects on child development. Despite the advantages, earlier studies also show that children present with higher cortisol levels in out-of-home childcare day when compared to days spent at home. However, only few studies have followed up the same children longitudinally. Furthermore, earlier studies have not included a comparison group of children, who were cared for at home. This study aimed at comparing children’s diurnal saliva cortisol output in outof-home childcare and in at-home parental care settings at the child age of 2 and 3.5 years old. Furthermore, the aim was to examine whether child temperament would moderate the associations between the childcare context and diurnal cortisol production. The participants were recruited from the FinnBrain Birth Cohort Study. The results showed that at the age of 2 years, the children presented with higher cortisol levels in at-home parental care when compared to the out-of-home childcare setting. However, these differences no longer appeared, as the children developed and reached the age of 3.5 years. When investigating the diurnal cortisol profiles, the results suggested higher afternoon cortisol levels in the out-of-home childcare group during the childcare day when compared to days spent at home. This difference appeared both at the age of 2 and 3.5 years old. Furthermore, temperamental surgency was associated with higher total diurnal cortisol production across the childcare settings. However, the association between surgency and diurnal cortisol production diminished along with the child age from 2 to 3.5 years of age. These findings have implications for understanding the periods of sensitivity in early childhood stress regulation and associations between temperament and cortisol output in different childcare settings.

Varhaislapsuuden stressinsäätely kotona ja varhaiskasvatuksessa – yhteydet lapsen temperamenttiin ja ikään – FinnBrain Syntymäkohorttitutkimus Aiemmat tutkimukset osoittavat, että päiväkodin varhaiskasvatus hyödyttää lapsia monin eri tavoin. Siitä huolimatta tutkimuksissa on havaittu, että kodin ulkopuolinen hoitoympäristö voi nostaa lasten kortisolihormonitasoja. Aiheesta ei ole juurikaan pitkittäistutkimusta, eivätkä aiemmat tutkimukset ole huomioineet kotihoidossa olevien lasten vertailuryhmää. Tämän väitöskirjan tavoitteena oli tutkia varhaislapsuuden stressinsäätelyä sekä kotihoidossa että varhaiskasvatukseen osallistuvilla lapsilla. Lasten kortisolitasoja mitattiin kotona ja päiväkodissa 2- ja 3,5-vuoden iässä. Lisäksi tutkittiin, onko lapsen temperementti yhteydessä lapsen kortisolitasoihin kotona tai päiväkodissa. Lapset valittiin mukaan FinnBrain Syntymäkohorttitutkimuksesta. Tulokset osoittavat, että 2-vuotiaiden lasten keskimääräiset kortisolitasot olivat korkeammat kotihoidossa kuin varhaiskasvatuksessa. Erot kuitenkin tasoittuivat lasten kasvaessa, eikä niitä havaittu enää 3,5-vuoden kohdalla. Varhaiskasvatukseen osallistuvien lasten kohdalla havaittiin lisäksi, että iltapäivän kortisolitasot olivat korkeammat päiväkodissa kuin kotipäivänä vastaavana ajankohtana. Tämä yhteys ilmeni sekä 2-vuotiaana että 3,5-vuoden iässä. Tutkimus osoitti myös, että kaikkein ulospäinsuuntautuneimmilla (ns. surgency/extroversion) lapsilla keskimääräiset kortisolitasot olivat 2-vuotiaana korkeammat sekä kotona että päiväkodissa. Yhteys kuitenkin heikkeni lasten kasvaessa, eikä sitä havaittu enää 3,5-vuoden kohdalla. Tutkimus antaa uutta tietoa lapsen stressinsäätelystä erilaisissa hoitoympäristöissä sekä lapsen iän vaikutuksesta kortisolihormonitasoihin. Tutkimus myös lisää ymmärrystä lapsen temperamenttipiirteiden yhteydestä stressinsäätelyyn sekä siihen liittyvistä herkkyysvaiheista.